Hindustan-Soviet Union Relations Before independence - Devi, Dharshana (Innovative Research Thoughts, 2018)
The economic and cultural relations of India and the Soviet Union are there since ancient times.1 But the diplomatic relations are new.2 Expenses of arid land and the almost impenetrable mountain ranges of Central Asia impose a formidable physical barrier between European Russia and the Indian subcontinent.3 A few traders and travellers made their way between the two regions as early as the twelfth century, but contacts over the years were extremely limited.4 There is ample evidence of this in the historical records of two countries.5 The relations between both the countries represented goodwill.6 The Russian writers obtained the first documents about the Indian information in the 11th and 12th centuries as translated in the Russian language from the Latin stories.7 They include the relations with India, comments on the prosperous country, stories, etc.